1993
DOI: 10.1159/000126608
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Aromatization of Testosterone in Mouse Hypothalamic Neurons

Abstract: Conversion of androgens to oestrogens by neural aromatase during brain development appears to be a prerequisite for sexual differentiation of the mammalian central nervous system. In order to investigate the pre- and perinatal patterns of testosterone (T) aromatization in the male and female mouse brain, aromatase activity (AA) was measured in hypothalamic and cerebral homogenates of embryonic day (ED) 17 fetuses and neonates using an in vitro 3H2O product formation microassay. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 33 publications
5
35
0
1
Order By: Relevance
“…Specifically, estrogens are implicated in the development of structural and functional sex differences in the Hyp/POA. It is important to note that estrogens are actively synthesized in the brain by the enzyme aromatase which is perinatally expressed in hypothalamic neurons, and that higher aromatase expression and estrogen synthesis rates are found in the male Hyp/POA [3, 17, 18, 19]. This led to the concept of estrogenic masculinization of the mammalian brain [1, 2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, estrogens are implicated in the development of structural and functional sex differences in the Hyp/POA. It is important to note that estrogens are actively synthesized in the brain by the enzyme aromatase which is perinatally expressed in hypothalamic neurons, and that higher aromatase expression and estrogen synthesis rates are found in the male Hyp/POA [3, 17, 18, 19]. This led to the concept of estrogenic masculinization of the mammalian brain [1, 2].…”
Section: Discussionmentioning
confidence: 99%
“…In the CNS, the classical ER-α is found in different brain regions including the Hyp/POA in adults and during development [6, 7, 20, 21]. Although estrogen synthesis is several times higher in the male hypothalamus compared to the female around birth [3, 17], inverse sex differences in the expression of the ER-α have been reported in the Hyp/POA with higher levels in females [7]. Moreover, it was suggested that estrogens downregulate the expression of its ER-α in the male Hyp/POA [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further support for the idea that male-oriented behavior in rams may result, in part, from variations in brain differentiation was the observation by Resko et al (Resko et al, 1996) that aromatase activity is significantly lower in the medial preoptic area of maleoriented than of female-oriented rams. Previous studies in rats demonstrated that the capacity for aromatization in the MPOA is a sexually differentiated characteristic of the brain that is organized by perinatal exposure to gonadal testosterone (Beyer et al, 1993;.…”
Section: Neurobiology Of Sexual Partner Preference In Ramsmentioning
confidence: 99%